Assessment and treatment of high‐risk challenging behavior of adolescents with autism in an aquatic setting. Issue 1 (18th June 2019) - Dowdy, Art; Tincani, Matt
Abstract : Aquatic‐based activities produce positive skill and health benefits for individuals with Autism Spectrum Disorder (ASD); however, aquatic contexts, such as the pool, introduce the risk of injury and drowning. This risk is heightened when individuals with ASD engage in challenging behavior in the pool context. The purpose of the study was to evaluate the effects of differential reinforcement without extinction for 2 participants diagnosed with ASD who engaged in challenging behavior when asked to transition from the pool. The treatment successfully decreased participants' transition latencies and challenging behavior during transitions from the pool for up to 2 months following treatment. Lifeguard staff rated the procedures as highly acceptable and helpful, and noted high degrees of satisfaction with improvements for each participant's behavior.